Detection of two alphaviruses: Middelburg virus and Sindbis virus from enzootic amplification cycles in southwestern Uganda - Graff, Selina Laura; Eibner, Georg Joachim; Ochieng, James Robert; Jones, Terry C.; Nsubuga, Anthony Mutebi; Lutwama, Julius Julian; Rwego, Innocent Bidason; Junglen, Sandra (Frontiers in Microbiology, 2024)
Our knowledge of alphavirus genetic diversity is mainly based on viruses isolated from anthropophilic mosquito species, humans, and livestock during outbreaks. Studies on alphaviruses from sylvatic amplification cycles in sub-Saharan Africa have been conducted less often than from epizootic environments. To gain insight into alphavirus diversity in enzootic transmission cycles, we collected over 23,000 mosquitoes in lowland rainforest and savannah gallery forest areas in southwestern Uganda and tested them for alphavirus infections. We detected Sindbis virus (SINV) in a Culex Culex sp. mosquito and Middelburg virus (MIDV) in Eretmapodites intermedius and Mansonia africana. MIDV is a mosquito-borne alphavirus that causes febrile illness in sheep, goats, and horses and was previously not known to occur in Uganda. SINV, also a mosquito-borne alphavirus, causes mild infections in humans. Full genomes of SINV and MIDV were sequenced, showing a nucleotide identity of 99% to related strains, respectively. Both isolates replicated to high titres in a wide variety of vertebrate cells. Our data suggest endemic circulation of SINV and MIDV in Uganda.